Impact-related deformation of zircon - Timms, N.; Erickson, T.; Cavosie, Aaron; Pearce, M.; Reddy, S.; Zanetti, M.; Tohver, E.; Schmieder, M.; Nemchin, A.; Wittmann, A. (WILEY-BLACKWELL, 2016)
In this presentation, impact-related deformation microstructures in zircon will be examined in detail, especially techniques to reliably identify them, and how relationships among them can be interpreted in terms of processes.